Columnar growth phenotype in apple results from gibberellin deficiency by ectopic expression of a dioxygenase gene. (25th April 2020) - Okada, Kazuma; Wada, Masato; Takebayashi, Yumiko; Kojima, Mikiko; Sakakibara, Hitoshi; Nakayasu, Masaru; Mizutani, Masaharu; Nakajima, Masatoshi; Moriya, Shigeki; Shimizu, Taku; Abe, Kazuyuki
Abstract: The apple cultivar McIntosh Wijcik, which is a mutant of 'McIntosh', exhibits a columnar growth phenotype (short internodes, few lateral branches, many spurs, etc.) that is controlled by a dominant Co gene. The candidate gene ( MdDOX-Co ), encoding a 2-oxoglutarate-dependent dioxygenase, is located adjacent to an insertion mutation. Non-columnar apples express MdDOX-Co in the roots, whereas columnar apples express MdDOX-Co in the aerial parts as well as in the roots. However, the function of MdDOX-Co remains unknown. Here, we characterized tobacco plants overexpressing MdDOX-Co . The tobacco plants showed the typical dwarf phenotype, which was restored by application of gibberellin A3 (GA3 ). Moreover, the dwarf tobacco plants had low concentrations of endogenous bioactive gibberellin A1 (GA1 ) and gibberellin A4 (GA4 ). Similarly, 'McIntosh Wijcik' contained low endogenous GA4 concentration and its dwarf traits (short main shoot and internodes) were partially reversed by GA3 application. These results indicate that MdDOX-Co is associated with bioactive GA deficiency. Interestingly, GA3 application to apple trees also resulted in an increased number of lateral branches and a decrease in flower bud number, indicating that gibberellin (GA) plays important roles in regulating apple tree architecture by affecting both lateral branch formation (vegetative growth) and flower bud formation (reproductive growth). We propose that a deficiency of bioactive GA by ectopic expression of MdDOX-Co in the aerial parts of columnar apples not only induces dwarf phenotypes but also inhibits lateral branch development and promotes flower bud formation, and assembly of these multiple phenotypes constructs the columnar tree form.